2015
DOI: 10.4067/s0034-98872015000700015
|View full text |Cite
|
Sign up to set email alerts
|

Relación entre el bienestar y el rendimiento académico en alumnos de primer año de medicina

Abstract: (Rev Med Chile 2015; 143: 930-937)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0
25

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 11 publications
1
12
0
25
Order By: Relevance
“…According to the JD-R model, engagement plays a mediating role in the relationship between job resources (e.g., job control and performance feedback) and positive organizational outcomes (e.g., commitment and job performance; for an overview see Schaufeli & Salanova, 2007b). Previous studies have shown that study engagement predicts academic achievement, amongst others, in terms of grade point average derived from university records (Casuso-Holgado et al, 2013;Gomez et al, 2015;Salanova et al, 2010). Additionally, and in accordance with the JD-R model, study engagement mediated the relationship between facilitators (e.g., organizational facilitators, social facilitators, and personal facilitators), on the one hand, and future performance, on the other (Salanova et al, 2010).…”
supporting
confidence: 66%
See 1 more Smart Citation
“…According to the JD-R model, engagement plays a mediating role in the relationship between job resources (e.g., job control and performance feedback) and positive organizational outcomes (e.g., commitment and job performance; for an overview see Schaufeli & Salanova, 2007b). Previous studies have shown that study engagement predicts academic achievement, amongst others, in terms of grade point average derived from university records (Casuso-Holgado et al, 2013;Gomez et al, 2015;Salanova et al, 2010). Additionally, and in accordance with the JD-R model, study engagement mediated the relationship between facilitators (e.g., organizational facilitators, social facilitators, and personal facilitators), on the one hand, and future performance, on the other (Salanova et al, 2010).…”
supporting
confidence: 66%
“…Because students' activities can be considered "work" from a psychological perspective, the job demands-resources (JD-R) model (Bakker & Demerouti, 2007;Schaufeli, Bakker, & Van Rhenen, 2009) can be applied to study engagement (Casuso-Holgado et al, 2013;Gomez et al, 2015;Salanova et al, 2010;Schaufeli, Martinez, et al, 2002). The JD-R model is an occupational stress model that suggests that strain is a response to an imbalance between job demands and job resources (Bakker & Demerouti, 2007;Schaufeli et al, 2009).…”
mentioning
confidence: 99%
“…Estos resultados, podrían apoyar la idea de que aquellos estudiantes universitarios que experimentan un estado agradable de inmersión frente a los estudios y que, a su vez, tienen un compromiso y una dedicación con los mismos, están más satisfechos con su experiencia académica (Caballero, Abello y Palacio, 2007). A su vez, ser capaz de entender los estudios como un reto positivo, disfrutar en las actividades relacionadas y persistir ante los contratiempos y dificultades de los mismos, lleva al estudiante a apreciar una mayor sensación de bienestar y un mejor desempeño y mayor satisfacción en el ámbito académico (Gómez et al, 2015;Wach, Ruffing, Brünken y Spinath, 2016).…”
Section: Discussionunclassified
“…El bienestar tiene impacto sobre los aspectos generales de la vida relacionadas con la salud; por ejemplo, en el trabajo (Blanch, 2014), en la pérdida de uno o la dificultad para conseguirlo (Evans-Lacko, Knapp, McCrone, Thornicroft, & Mojtabai, 2013); en el rendimiento académico (Gómez et al, 2015); en la participación social (Coppari, et al, 2013), entre otros.…”
Section: Salud Mental Y Bienestarunclassified